2017
DOI: 10.1007/978-1-4939-7057-5_21
|View full text |Cite
|
Sign up to set email alerts
|

Serum Profiling for Identification of Autoantibody Signatures in Diseases Using Protein Microarrays

Abstract: Protein microarrays are platforms for studying protein-protein interactions and identifying disease-related self-antigens/autoantigens, which elicit an immune response in a high-throughput format. Protein arrays have been extensively used over the past two decades for several clinical applications. By using this platform, serum containing autoantibodies against potential self-antigens can be screened on proteome-wide arrays, harboring a large repertoire of full-length human proteins. Identification of such aut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…This perturbation subsequently results in defects in immune tolerance, inflammation, and cellular death mechanisms [11]. All these bioprocesses lead to the development of tumor-associated antigens (TA) that evoke an immune response and subsequent generation of antibodies against self-proteins, called TA autoantibodies (AAbs) [12][13][14]. The autoantibody production reflects greater immunological actions and advanced immunosurveillance in CRC patients.…”
Section: Introductionmentioning
confidence: 99%
“…This perturbation subsequently results in defects in immune tolerance, inflammation, and cellular death mechanisms [11]. All these bioprocesses lead to the development of tumor-associated antigens (TA) that evoke an immune response and subsequent generation of antibodies against self-proteins, called TA autoantibodies (AAbs) [12][13][14]. The autoantibody production reflects greater immunological actions and advanced immunosurveillance in CRC patients.…”
Section: Introductionmentioning
confidence: 99%
“…Over the last two decades, high-density protein microarrays have been used for several clinical applications. Clinical samples like serum have been used to study autoantibodies against potential self-antigens, thus helping in early diagnostics, identifying prognostic markers and studying autoimmune disorders and systemic diseases [13]. Several studies in this field have identified potential autoantibody biomarkers for different types of tumours, including gastric cancer, lung cancer, brain tumours and breast cancer [14,15].…”
Section: Introductionmentioning
confidence: 99%